2021
DOI: 10.30654/mjd.10027
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Digital Radiography and Novel Diagnostic Tools versus Visual ICDAS Criteria: A Systematic Review

Abstract: Purpose: To evaluate the diagnostic accuracy of digital radiography and other novel diagnostic tools compared to visual ICDAS criteria. Materials and Methods:Two reviewers performed a literature search up to May 2020 in three databases: PubMed, Google Scholar, and Cochrane Library. Only in-vivo studies that evaluated the diagnostic accuracy of digital radiography, Diagnodent, Vistaproof, Soprolife, and ICDAS criteria were included.Results: A total of 27 in vivo studies were included in the systematic review. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…In vitro data suggested that laser fluorescence and visual inspection have similar accuracy. [ 9 13 ] There are limited evidence-based data in the literature regarding in vivo diagnostic accuracy of noncavitated carious lesions detection methods. In a previous systematic review[ 4 ] based on in vivo data, only 5 studies were eligible for meta-analysis and there was only one study assessing diagnostic accuracy of laser fluorescence (DIAGNOpen) for detection of noncavitated lesions in smooth facial surfaces with sensitivity and specificity of 0.32–0.78 and 0.64–0.85, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro data suggested that laser fluorescence and visual inspection have similar accuracy. [ 9 13 ] There are limited evidence-based data in the literature regarding in vivo diagnostic accuracy of noncavitated carious lesions detection methods. In a previous systematic review[ 4 ] based on in vivo data, only 5 studies were eligible for meta-analysis and there was only one study assessing diagnostic accuracy of laser fluorescence (DIAGNOpen) for detection of noncavitated lesions in smooth facial surfaces with sensitivity and specificity of 0.32–0.78 and 0.64–0.85, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] The DIAGNOdent detects carious lesions through quantifying bacterial by-products (porphyrins) produced by cariogenic bacteria and detecting their biological fluorescence. [ 20 ] Furthermore, previous systematic reviews[ 13 21 ] and other in vitro studies[ 16 17 18 22 23 ] showed that laser fluorescence detection methods such as DIAGNOdent and DIAGNOdent Pen had high in vitro sensitivity and specificity for detecting initial white spot lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro data suggested that laser uorescence and visual inspection have similar accuracy [11]. There is limited evidencebased data in the literature regarding in vivo diagnostic accuracy of non cavitated carious lesions detection methods.…”
Section: Discussionmentioning
confidence: 99%
“…The DIAGNOdent detects carious lesions through quantifying bacterial by-products (porphyrins) produced by cariogenic bacteria and detecting their biological uorescence [18]. Furthermore, previous systematic reviews [11,19] and other in vitro studies [14-16, 20, 21] showed that laser uorescence detection methods such as DIAGNOdent and DIAGNOdent Pen had high in vitro sensitivity and speci city for detecting initial white spot lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Различные авторы в своих исследованиях не пришли к единому мнению относительно наибольшей эффективности того или иного метода. Так, по результатам исследований одних авторов, критерии системы визуальной оценки ICDAS показали большую точность, чем устройства лазерной флуоресценции (DIAGNOdent pen) и трансиллюминации (VistaCam iX) [5], в то время как, по мнению других авторов, DIAGNOdent pen был более чувствительным инструментом для диагностики кариеса эмали и дентина по сравнению с визуальной шкалой ICDAS [22,37]. Тем не менее современные диагностические методы с достаточным уровнем чувствительности и специфичности, доступные сегодня клиницистам, значительно расширяют возможности раннего выявления окклюзионного кариеса.…”
Section: флуоресцентные методыunclassified